Is the development of arrhythmia predictable in rheumatoid arthritis? - Gulkesen, Arif; Uslu, Emine Yildirim; Akgol, Gurkan; Alkan, Gokhan; Kobat, Mehmet Ali; Gelen, Mehmet Ali; Uslu, Muhammed Fuad (Turkish League Against Rheumatism, 2024)
Objectives: This study aimed to determine whether there is a difference in the electrocardiography (ECG) measurements of healthy controls and rheumatoid arthritis (RA) patients and to predict whether they can be used to determine the risk of arrhythmia in patients. Patients and methods: The prospective study included 50 cardiac asymptomatic RA patients (38 males, 12 females; mean age: 46.8 +/- 9.1 years; range, 18 to 60 years) who met the 2010 American College of Rheumatology/European Alliance of Associations for Rheumatology RA criteria and 50 healthy volunteers (34 males, 16 females; mean age: 43.4 +/- 10.4 years; range, 18 to 60 years) as a control group between June 1, 2022, and August 31, 2022. Disease activity of the patients was calculated with the Disase Activity Score (DAS28). Heart rate, minimum and maximum QT intervals, QT dispersion, minimum and maximum P waves, P wave dispersion (Pd), minimum and maximum Tp-e intervals, Tp-e dispersion, minimum and maximum corrected QT (QTc) intervals, QTc dispersion, and the Tp-e/QTc ratio in ECGs were calculated. Results: The mean disease duration of the RA group was 9.09 +/- 5.74 years. The mean C-reactive protein level was 9.83 +/- 8.29, the mean erythrocyte sedimentation rate was 26.12 +/- 16.28 mm/h, and the mean DAS28 was 3.03 +/- 0.37. There was a statistically significant increase in the maximum P wave, Pd, maximum QT, QT dispersion, maximum QTc, QTc dispersion, maximum Tp-e, Tp-e dispersion, and Tp-e/QTc dispersion parameters in the RA group compared to the control group, while there was a significant decrease in the minimum P wave, minimum QT, and minimum QTc parameters. Conclusion: In our study, the Pd, QTc dispersion, Tp-e dispersion, and Tp-e/QTc dispersion values of our patients, which indicate the risk of atrial and ventricular arrhythmia, were found to be significantly higher. This finding suggests that our patients had an increased risk of cardiac morbidity and mortality. Arrhythmias are the likely source of the increase in sudden cardiac death in RA, and these new indicators measured on ECG can be used as standardized cardiovascular morbidity and mortality indicators in the future.
Keywords: Arrhythmia; electrocardiography; rheumatoid arthritis